Advancements in research on fluid overload in preterm infants—a narrative review - Liu, Xinyi; Deng, Shuyue; Chen, Siyu; Wan, Linxiao; Dong, Wenbin; Kang, Lan (Frontiers in Pediatrics, 2026)
ObjectiveFluid overload (FO) is a prevalent clinical challenge in preterm infants, contributing to multiorgan dysfunction and adverse outcomes. This review synthesizes the pathophysiology, clinical implications, and management strategies of FO to advance fluid management in preterm neonates.MethodsWe reviewed literature to define FO criteria, delineate its mechanisms (e.g., renal immaturity, endothelial glycocalyx impairment), and analyze associations with systemic complications. Current monitoring technologies and therapeutic interventions were evaluated. As a narrative review, literature identification and data extraction were conducted based on the research question and inclusion criteria without adhering to formal systematic review guidelines. All original studies cited in this review reported obtaining approval from institutional ethics committees and informed consent from parents or guardians. As a secondary analysis of published literature, this study does not involve new patient data and therefore required no additional ethical approval.ResultsFO pathogenesis involves underdeveloped renal function, compromised skin barriers, glycocalyx damage, and hypoalbuminemia. FO can lead to multisystem adverse outcomes. Noninvasive monitoring—echocardiography, bioelectrical impedance analysis (BIA), and lung ultrasound—demonstrates high clinical utility. Effective management includes strict fluid restriction, diuretic, and albumin infusion.ConclusionOptimizing FO management requires multimodal monitoring and individualized fluid regimens. Future research should prioritize refining assessment standards and developing targeted interventions to improve neonatal outcomes.